Analysis for Computer Scientists - Oberguggenberger, Michael; Ostermann, Alexander (Springer, 2018)
We are happy that Springer Verlag asked us to prepare the second edition of our textbook Analysis for Computer Scientists. We are still convinced that the algorithmic approach developed in the first edition is an appropriate concept for presenting the subject of analysis. Accordingly, there was no need to make larger changes. However, we took the opportunity to add and update some material. In particular, we added hyperbolic functions and gave some more details on curves and surfaces in space. Two new sections have been added: One on second-order differential equations and one on the pendulum equation. Moreover, the exercise sections have been extended considerably. Statistical data have been updated where appropriate. Due to the essential importance of the MATLAB programs for our concept, we have decided to provide these programs additionally in Python for the users’ convenience. We thank the editors of Springer, especially Simon Rees and Wayne Wheeler, for their support during the preparation of the second edition.
Foundations, Methods, and Algorithms